2018
DOI: 10.1111/acer.13888
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake Interacts with CDKAL1, HHEX, and OAS3 Genetic Variants, Associated with the Risk of Type 2 Diabetes by Lowering Insulin Secretion in Korean Adults

Abstract: Subjects with a High-GRS had an elevated risk of T2DM even with moderate alcohol intakes due to lower HOMA-B. High alcohol intake appears to be a risk factor for all Asians regardless of alcohol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…Few studies have focused on the interaction of alcohol with the genetic risk related to beta cell function. A Korean study reported that alcohol interacted with BC-related genetic variants but lowered insulin secretion [23]. Further well-powered studies investigating potential interactions are highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on the interaction of alcohol with the genetic risk related to beta cell function. A Korean study reported that alcohol interacted with BC-related genetic variants but lowered insulin secretion [23]. Further well-powered studies investigating potential interactions are highly warranted.…”
Section: Discussionmentioning
confidence: 99%
“…DEGs in GO terms and pathways might be linked with advancement of obesity associated type 2 diabetes mellitus. ERBB2 [36], DACT1 [37], ARAP1 [38], MYH9 [39], INPPL1 [40], SARM1 [41], NOTCH1 [42], ROBO1 [43], MAPK8IP1 [44], ANK1 [45], SARM1 [46], SREBF2 [47], SIK1 [48], PASK (PAS domain containing serine/threonine kinase) [49], NOS2 [50], OAS3 [51], KL (klotho) [52], PECAM1 [53], S100A12 [54], S100P [55], BATF3 [56], PLEK (pleckstrin) [57], ALOX5 [58], ARG1 [59], CXCL8 [60], CXCR1 [61], PTAFR (platelet activating factor receptor) [62], PYGL (glycogen phosphorylase L) [63], TCF4 [64], CAMP (cathelicidin antimicrobial peptide) [65], RUNX2 [66], PLA2G2A [67], GCG (glucagon) [68], RARRES2 [69] and HAP1 [70] were involved in the genesis of type 2 diabetes mellitus. Recent studies have reported that ACHE (acetylcholinesterase) [71], FGFR3 [72], VLDLR (very low density lipoprotein receptor) [73], SHC1 [74], HDAC6 [75], CHRNA2 [76], CASR (calcium sensing receptor) [77], ELK1 [78], TYK2 [79], CIITA (class II major histocompatibility complex transactivator) [80], ZAP70 [81], GPT (glutamic--pyruvic transaminase) [82], CHI3L1 [83], AIF1 [84], MMP9 [85], ITGB2 [86], CFD (complement factor D) [87], C3AR1 [88], LGALS1 [89], CD14 [90], TIMP1 [91], TLR2 [92], LTF (lactotransferrin) [93], BRCA2 [94] and IGFBP3 [95] promotes the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Steinthorsdottir et al [ 16 ] reported that homozygous carriers of the risk allele G of rs7756992 had a 22% decreased insulin response to glucose load than A/A allele carriers. Previous findings suggest significant associations between CDKAL1 , alcohol intake, dietary fat, and energy intake in relation to diabetes [ 23 , 36 , 37 ]. In the Ansan/Ansung Korean cohort, diabetes risk increased by 1.549 (95% CI 1.207–1.720) when high alcohol intake was combined with the presence of CDKAL1 risk alleles [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest significant associations between CDKAL1 , alcohol intake, dietary fat, and energy intake in relation to diabetes [ 23 , 36 , 37 ]. In the Ansan/Ansung Korean cohort, diabetes risk increased by 1.549 (95% CI 1.207–1.720) when high alcohol intake was combined with the presence of CDKAL1 risk alleles [ 36 ]. In Japanese men, the interaction between CDKAL1 gene variants and excessive energy intake increased glycated hemoglobin ( p = 0.037) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%